PENGARUH KOMPENSASI, MOTIVASI, DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI PTDI-STTD KABUPATEN BEKASI DIVISI FUNGSIONAL UMUM - Hidayatulloh, Wendy; Ananda, Denta Felli (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This research was conducted to find out the influence of Compensation, Motivation, and Communication on the Performance of PTDI-STTD Employees, Bekasi District, General Functional Division. This research uses quantitative research methods with a causality approach. The study used saturated sampling. The respondents used were as many as 80 employees of PTDI-STTD general functional division. In this study conducted the dissemination of questionnaires. The result of this study is that the variable Compensation and motivation individually do not have a significant influence on employee performance while communication has a significant influence on employee performance Keywords: Compensation, Motivation, Communication and Employee Performance